Sustainable development of Polish cities – case study of Wrocław - Krześ, Agnieszka (Zrównoważony rozwój polskich miast na przykładzie Wrocławia, 2024)
Aim: The aim of this paper is to assess the achievements of goal 11 of Agenda 2030 halfway through the time frame of the adopted resolution. Considerations are undertaken using, as an example, Wrocław, one of the most important Polish metropolises. Methodology: The paper uses critical analysis of the literature and strategic documents, as well as statistical analysis. Sustainable development is considered from three aspects: economic, social and environmental. A review is also conducted of actions implemented by the Wrocław authorities that have contributed to achieving the city’s sustainable development. Results: Thanks to a high level of socio-economic development it is possible to implement a range of initiatives aimed at improving the natural environment and the rational use of resources, however, despite the actions taken, achieving sustainable development remains in the sphere of long-term strategic plans. Implications and recommendations: In an era of increasing urbanization, ever more attention is focused on cities. By accumulating capital, population and cultural and art institutions within their territory, they become the driving force of socio-economic development. However, for many years this development was at the cost of the natural environment. In this context, goal 11 of the United Nations’ Agenda for sustainable development to the year 2030 is of particular importance. This goal focuses on the sustainable development of cities, their safety and social inclusion. Polish cities also face the challenge of implementing the ideas of sustainable development.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 105-115
Keywords: sustainable development; Sustainable Development Goals; Agenda 2030; city; Wroclaw; zrównoważony rozwój; cele zrównoważonego rozwoju; miasto; Wrocław